HPLC Evaluation of Phenolic Profile, Nutritive Content, and Antioxidant Capacity of Extracts Obtained from Punica granatum Fruit Peel - Sushil Kumar Middha; Talambedu Usha; Veena Pande (Hindawi Limited, 2013)
This study revealed polyphenolic content, nutritive content, antioxidant activity, and phenolic profile of methanol and aqueous extracts of Punica granatum peel extract. For this, extracts were screened for possible antioxidant activities by free radical scavenging activity (DPPH), hydrogen peroxide scavenging activity and ferric-reducing antioxidant power (FRAP) assays. The total phenolics and flavonoid recovered by methanolic (MPE) and the water extract (AQPE) were ranged from 185 ± 12.45 to 298.00 ± 24.86 mg GAE (gallic acid equivalents)/gm and 23.05 ± 1.54 to 49.8 ± 2.14 quercetin (QE) mg/g, respectively. The EC50 of herbal extracts ranged from 100 µg/ml (0.38 quercetin equivalents), for AQPE, 168 µg/ml (0.80 quercetin equivalents), for MPE. The phenolic profile in the methanolic extracts was investigated by chromatographic (HPLC) method. About 5 different flavonoids, phenolic acids, and their derivatives including quercetin (1), rutin (2), gallic acid (3), ellagic acid (4), and punicalagin as a major ellagitannin (5) have been identified. Among both extracts, methanolic extract was the most effective. This report may be the first to show nutritive content and correlation analysis to suggest that phenols and flavonoids might contribute the high antioxidant activity of this fruit peel and establish it as a valuable natural antioxidant source applicable in the health food industry.